Effect of aramid core-spun yarn on impact resistance of aramid/epoxy composite - Yajing Miao; Jiahuan Ni; Jiahuan Ni; Jiahuan Ni; Kai Zhu; Kai Zhu; Yizhou Liu; Yizhou Liu; Yu Chang; Yu Chang; Zixin Gong; Zixin Gong; et al. (Frontiers in Materials, 2023)
Introduction: The surface of aramid filament is smooth, which is a great defect for impact resistance and composite molding of aramid/epoxy composite. In this study, a new type of yarn—aramid core-spun yarn is introduced to the fabrication of compositematerials. It increases the friction among yarns and optimizes the performance of yarns.Methods: To verify the improvement of yarn in the composite material, the hand lay-up process is used, and the first layer and the fourth layer are replaced by core-spun yarns in a four-layer composite configuration.Results and Discussion: The energy absorption, and the damage of the impacted surface and the back surface are evaluated through the drop weight impact test. The yarn pull-out test can reflect the internal friction of fabric. The results show that the average energy absorption of new yarn in the first layer is 10 J cm2/g more than that in the fourth layer at a 90°/45°/-45°/0° configuration after the normalization, but the conclusion is contrary when the structure is -45°/0°/90°/45°. Under the structure of 90°/45°/-45°/0°, the damaged area of the fabric is larger when the aramid core-spun yarn is laid on the first layer, while a contrary result can be found for the structure of -45°/0°/90°/45°. The fundamental research will provide design ideas and supports for aramid composite.